The Effect Of Telemedicine And Service Quality On Switching Intention Through Patient Satisfaction And Patient Trust In Type C Public Hospitals In Banjarmasin, South Kalimantan - Julius Henry; Anita Lie; Christina Esti (Publikasi Indonesia, 2024)
The increasingly fierce competition conditions pose its own problems for hospitals, namely how hospitals operate effectively and efficiently in order to survive and develop. The factor that needs attention from the hospital management is the desire of the patient to move to another hospital service or known as switching intention. Therefore, hospital management is required to be able to effectively manage all resources and, especially in the field of technology, so that hospital profitability does not fall. One form of technology utilization that is being widely developed for the health and hospital fields is telemedicine. This study was conducted with the aim of knowing and analyzing effect of telemedicine and service quality towards switching intention with patient satisfaction and patient trust as intervening variables. The method used in this study is a quantitative descriptive research method with a causal approach, with a sample of 335 respondents. Based on research findings, it is proven that there is a positive and significant influence of telemedicine on satisfaction and trust, service quality on inpatient satisfaction and trust, and there is a negative and significant influence of patient satisfaction and trust on switching intention at Class C Private General Hospitals in South Kalimantan. For this reason, it is necessary to increase the use of telemedicine between the hospital through doctors and patients or patients' families so that they can communicate online. Improvement in service quality also needs to be maintained and improved so that this can increase patient satisfaction and trust in the hospital.